Optimum design of structures against earthquake by wavelet neural network and filter banks. - Salajegheh, Eysa (Earthquake engineering & structural dynamics.)
Optimum design of structures for earthquake is achieved by simulated annealing. To reduce the computational work, a fast wavelet transform is used by means of which the number of points in the earthquake record is decreased. The record is decomposed into two parts. One part contains the low frequency of the recrd, and the other contains the high frequency of the record. The low frequency content is the effective part, since most of the energy of the record is contained in this part of the record. Thus, the low frequency part of the record is used for dynamic analysis. Then, using a wavelet neural network, the dynamic responses of the structures are approximated. By such approximation, the dynamic analysis of the structure becomes unnecessary in the process of optimization. The wavelet neural networks have been employed as a general approximation tool for the time history dynamic analysis. A number of structures are designed for optimal weight and the results are compared to those corresponding to the exact dynamic analysis.